Absurdist marketing, radical honesty, and entrepreneurial brand leadership: a netnographic study of the aldis burger phenomenon in Indonesia - Udin Saryono; Yulianto Yulianto; Ema Trisnawati; Taryati Sukmawati; Devi Wahyuningsih (Enrichment : Journal of Management, 2026)
This study examines how unconventional brand communication and entrepreneurial leadership jointly shape consumer trust in digital marketing. Using a contextual netnographic approach, 200 purposively sampled Instagram comments from five high-engagement Aldis Burger posts during its peak viral period (Q1–Q2 2026) were analyzed using thematic analysis. Five dominant themes emerged: Trust (30%), Humor (24%), Persona (20%), Uniqueness (14%), and Skepticism (12%), each reflecting a distinct leadership dimension. The findings indicate that entrepreneurial brand communication functions not only as a marketing strategy but also as an expression of leadership that strengthens consumer trust. Building on these findings, the study proposes three theoretically grounded constructs—Performative Honesty, Absurd Credibility, and Anti-Competitive Trust Signaling—together with the Persona-Congruence Mechanism as a moderating condition for trust formation. These constructs are presented as testable propositions for future research. The study contributes to the literature on brand leadership, digital marketing authenticity, and consumer trust while offering practical insights for entrepreneurial branding in the digital economy